Efficacy of a topical gabapentin gel in a cisplatin paradigm of chemotherapy-induced peripheral neuropathy - Muhammad Shahid; Fazal Subhan; Nisar Ahmad; Robert D. E. Sewell (BMC, 2019)
Abstract Background Chemotherapy induced peripheral neuropathy (CIPN) has been attributed to chemotherapeutic agents such as cisplatin which adversely affect disease outcome leading to increased cancer related morbidity. The clinical efficacy of systemic gabapentin in neuropathic pain management is limited by central side-effects in addition to a scarceness of conclusive evidence of its efficacy in CIPN management. The topical route therefore may provide a relatively safe alternative for neuropathic pain treatment in general and CIPN in particular. Methods Cisplatin induced neuropathic nociception was established in rats after a single weekly cisplatin injection (3.0 mg/kg, intraperitoneally) for 4 weeks. The evoked neuropathic sensation of allodynia was assessed by plantar application of von Frey monofilaments as the paw withdrawal threshold (PWT), whereas the expression of heat-hypoalgesia was determined on a hot-plate as paw withdrawal latency (PWL). Gabapentin gel (10% w/w) was applied three-times daily on the hind paws while in a concurrent systemic study, gabapentin was administered daily (75 mg/kg, intraperitoneally) for 4 weeks. To assess any evidence of neurological adverse symptoms of cisplatin and the central side-effect propensity of systemic or topical gabapentin, evaluation of motor coordination (rotarod test) and gait (footprint analysis) were performed. Results Cisplatin invoked a progressive development of neuropathic hind paw allodynia (decreased PWT, days 7-28) and heat hypoalgesia (increased PWL, days 21-28). Topical gabapentin significantly delayed the expression of both allodynia on protocol days 21 and 28 and heat-hypoalgesia (day 28). Systemic gabapentin displayed a comparative anti-neuropathic predisposition through a sustained suppression of tactile allodynia on days 14 and 21-28 as well as thermal hypoalgesia (days 21 and 28). Systemic gabapentin also impaired motor coordination and gait thus affirming its clinically documented central side effects, but these outcomes were not evident after topical treatment. Conclusions Both topical and systemic gabapentin exhibit a propensity to attenuate CIPN in a cisplatin paradigm. Gabapentin applied topically may therefore provide an adjunctive or alternative route for CIPN management upon cessation of systemic medications due to intolerable side-effects.